Study on the mechanical behavior and fracturing mechanism of rock containing two unparallel prefabricated fissures under uniaxial loading - Jian Li; Yunyun Wei; Tie Wang (PLoS ONE, 2026)
As a natural material, rock is widely used in construction and building engineering, such as wall brick and road foundations. However, natural rock usually contains fissures and fractures, which greatly affect the long-term structural stability. In this paper, the mechanical behavior and fracturing mechanism of red sandstone containing two unparallel prefabricated fissures under uniaxial loading are studied using the finite-discrete element method (FDEM), and the modeling results are compared with the experimental results. Firstly, the uniaxial compression tests on the intact red sandstone are conducted to calibrate the input parameters in FDEM, which are validated against experimental stress-strain curves and failure modes. Then, a series of uniaxial compression numerical models of rock samples containing two fissures with different angles ( β 2 ) of the second fissure are established. Finally, the influence of β 2 on the stress-strain curve, crack number and acoustic emission (AE) characteristics, failure mode, stress and displacement fields and energy evolution during uniaxial compression is discussed. Results indicate that the uniaxial compressive strength (UCS), peak strain and Young’s modulus all increase first and then decrease with the increase of β 2 . Especially, these indexes have a maximum value when β 2 = 90°, and have the smallest value with a β 2 of 180°. The material exhibits progressive failure characteristics when β 2 = 180° based on AE singles but brittle failure is dominant in other cases. Generally, shear failure is concentrated at the fissure tips, while tensile failure mainly occurs in the complete zone inside the specimen. Besides, the evolution of peak strain energy with β 2 is the same as the changing trend of the above indexes, but the kinetic energy shows a decreasing trend as β 2 increases. The stress and displacement fields before cracking can well explain the crack propagation and intersection mechanism. The simulated failure mode and crack morphology reproduce most of the phenomena observed in the laboratory test. The results in this paper provide theoretical support for the design of deformation and bearing capacity of fractured red sandstone-based projects such as fractured rock mass tunnel.